2010
DOI: 10.1353/jhr.2010.0018
|View full text |Cite
|
Sign up to set email alerts
|

Health and Wages: Panel Data Estimates Considering Selection and Endogeneity

Abstract: This paper complements previous studies on the effects of health on wages by addressing the problems of unobserved heterogeneity, sample selection, and endogeneity in one comprehensive framework. Using data from the German Socio-Economic Panel (GSOEP) we find the health variable to suffer from measurement error and a number of tests provide evidence that selection corrections are necessary. Good health leads to higher wages for men, while there appears to be no significant effect for women. Contingent on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 33 publications
(37 reference statements)
4
62
0
1
Order By: Relevance
“…In particular, it could be shown that health has an impact on wages in Germany (Jäckle and Himmler 2010 for the second and for the third course. The reason why this can be done is that the question on cancelling courses is not only posed to non-participants in the WeLL data but also to…”
Section: Empirical Methodsmentioning
confidence: 99%
“…In particular, it could be shown that health has an impact on wages in Germany (Jäckle and Himmler 2010 for the second and for the third course. The reason why this can be done is that the question on cancelling courses is not only posed to non-participants in the WeLL data but also to…”
Section: Empirical Methodsmentioning
confidence: 99%
“…21 I report standard OLS and FE results for comparison. 22 This result differs from the findings in Jäckle and Himmler (2010). Using the SOEP, Jäckle and Himmler (2010) estimate a similar wage model with health satisfaction instead of general health status.…”
mentioning
confidence: 86%
“…These objective health measures are less prone to measurement errors and the issue of endogeneity-problems that may occur using the self-reported health status (cf. Jäckle 2007). Unfortunately, the information about the numbers of nights stayed in hospital is not available for 1990 or 1993 so that we are not able to use the respective waves.…”
Section: Datamentioning
confidence: 99%